PENGARUH MEDIA PROMOSI KESEHATAN BERBASIS MULTI LEVEL HEALTH PROMOTION TERHADAP INTENSI DAN PERILAKU MEROKOK SANTRI DI PONDOK PESANTREN API JAWA TENGAH - wijayanti, punik mumpuni (PRIMA EKONOMIKA, 2021)
The number of active smokers in Indonesia always increases every year and the age of active smokers commonly adolescents between 10-18 years. One of the cigarette consumption control programs is the smoking cessation clinic and non-smoking areas. Local regulations about non-smoking areas have not been fully effective in the education area, especially in Magelang. An effective model of health promotion is expected to change the intention and behavior of adolescents about smoking. The purpose of this study was to determine effect of health promotion model on santri’s intention and behavior at the Islamic Boarding School, Magelang. Study design was experimental using one group pre test-post test design. A total of 95 santri participated in the study and were given interventions in the form of lectures, discussions, videos and posters. Intention and behavior of santri was obtained using a questionnaire and Wilcoxon sign test to analyze the effect of health promotion on santri's knowledge and behavior. Most santri smoke (68.8%) and based on Wilcoxon sign test showed there are significanly differences in intention and smoking behavior of students after being given a health promotion (p<0.001). The health promotion model non-smoking areas significantly influences santri’s intention and behavior. Keywords : Health Promotion, Intention, Behavior